2016
DOI: 10.1038/srep37442
|View full text |Cite
|
Sign up to set email alerts
|

Second-trimester urine nephrin:creatinine ratio versus soluble fms-like tyrosine kinase-1:placental growth factor ratio for prediction of preeclampsia among asymptomatic women

Abstract: This prospective observational study compare urine nephrin:creatinine ratio (NCR, ng/mg) with serum soluble fms-like tyrosine kinase-1:placental growth factor ratio (FPR, pg/pg) for preeclampsia (PE) prediction among unselected asymptomatic pregnant women in 2nd trimester. NCR and FPR were determined in 254 paired urine/blood samples collected simultaneously from 254 women at median gestational week (GW) 24 (range, 22–27) without hypertension or significant proteinuria in pregnancy (SPIP). Fifteen (5.9%) devel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…Therefore, an important aspect to include in a meta-analysis such as this is the heterogeneity in diagnostic accuracy of the methods employed by the various studies. ELISA was the method of choice in most studies (n = 11) for the detection of nephrinuria in PE and nephropathies [20,24,25,31,32,36,43,45,[48][49][50]. Interestingly these assays demonstrated improved sensitivity (0.89) and specificity (0.73) and therefore diagnostic accuracy (AUC-SROC = 0.92) for determining urinary nephrin compared to RT-PCR [44,46,47].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, an important aspect to include in a meta-analysis such as this is the heterogeneity in diagnostic accuracy of the methods employed by the various studies. ELISA was the method of choice in most studies (n = 11) for the detection of nephrinuria in PE and nephropathies [20,24,25,31,32,36,43,45,[48][49][50]. Interestingly these assays demonstrated improved sensitivity (0.89) and specificity (0.73) and therefore diagnostic accuracy (AUC-SROC = 0.92) for determining urinary nephrin compared to RT-PCR [44,46,47].…”
Section: Discussionmentioning
confidence: 99%
“…An analysis of the 15 selected studies revealed that all studies aimed to investigate urinary nephrin as an early indicator of glomerular damage in both acute and chronic conditions. Eight studies utilised urinary nephrin for predicting PE [20,25,27,31,32,[43][44][45], six studies utilised urinary nephrin for predicting nephropathy [24,36,[46][47][48][49], and one study utilised urinary nephrin for predicting glomerulopathy/ glomerular injury [50]. Most of the studies used Enzyme Linked Immunosorbent Assay (ELISA) (n = 11) and the remaining used Real Time-Polymerase Chain Reaction (RT-PCR) (n = 3), and Western Blotting (WB) (n = 1) to determine the concentration of urinary nephrin.…”
Section: Characteristics Of Studies Included For Reviewmentioning
confidence: 99%
“…Thus, the ratio of sFlt-1 (i.e., anti-angiogenic factor) to PlGF (i.e., angiogenic factor) has been shown to increase before the onset of clinical signs and symptoms of PE. 6,[12][13][14][15][16][17] The sFlt-1/PlGF ratio is used as a tool to predict, diagnose, and manage PE in pregnant women suspected of having PE in several countries. [18][19][20][21] This test is now approved for use but is not yet routinely used in Japan.…”
Section: Introductionmentioning
confidence: 99%